Benefit perceptions and their influence on the willingness to join community supported agriculture (CSA) - Stefan Galley; Rita Saleh; Patrick Bottazzi (Cleaner and Responsible Consumption)
In this study, we focus on non-members’ benefit perception of Community Supported Agriculture (CSA) and their willingness to join. We look into how information impacts the perception of CSA benefits, their relevance, and how these benefits and other factors such as trust levels, subjective knowledge, sustainable food shopping behaviour, political orientation and socio-demographics, influence the willingness to join. We conducted an online between-subject experiment. Respondents (N = 754) were divided in six groups, five groups were exposed to one benefit of CSA (i.e., either to the nutritional, sustainability, solidarity, transparency or community benefit) each, with the sixth group being the control group. Our experiment revealed that regardless of the information given, farmers were perceived to benefit the most from CSA, followed by society and lastly by the individual. However, all participants ranked individual benefits and environmental sustainability as most important for them, followed by solidarity with farmers, transparency and community aspects. Moreover, the results show that the more beneficial CSAs are seen, the higher the willingness to join. While information on benefits such as solidarity with farmers, nutritional quality and community are effective in reaching young, educated and often female members, nutritional benefits are addressing environmentally conscious and conservative consumers. Overall, information on nutrition and environmental sustainability led to the highest wilingness to join. By communicating primarily about the nutritional benefits and environmental sustainability of CSAs, and not only about altruistic benefits, a wider spread and integration of CSA could be achieved, ultimately fostering a sustainable food production and consumption mindset.